Geographic and intra‐racial disparities in early‐onset colorectal cancer in the SEER 18 registries of the United States. (22nd October 2020) - Abualkhair, Wesal H.; Zhou, Meijiao; Ochoa, Carolina O.; Lacayo, Leonel; Murphy, Caitlin; Wu, Xiao‐Cheng; Karlitz, Jordan J.
Abstract: Background: Although early‐onset colorectal cancer (EOCRC) incidence rates (IRs) are increasing, geographic and intra‐racial IR disparities are not well defined. Methods: 2000‐2015 Surveillance, Epidemiology, and End Results (SEER) program CRC IR Analysis (170, 434 cases) was performed from ages 30 to 60 in four US regions, 18 individual registries, metropolitan and nonmetropolitan locations and stratified by race. Analyses were conducted in 1‐year and 5‐year age increments. Results: Wide US regional EOCRC IR variations exist: For example, age 45 IRs in the south are 26.8/100, 000, 36.0% higher than the West, 19.7/100, 000 ( p < 0.0001). Disparities magnify between individual registries: EOCRC IRs in highest risk registries were 177‐348% (Alaska Natives), 75‐200% (Hawaii), 76‐128% (Louisiana), and 61‐125% (Kentucky) higher than lowest risk registries depending on age. EOCRC IRs are 18.2%‐25.6% higher in nonmetropolitan versus metropolitan settings. Wide geographic intra‐racial disparities exist. Within the White population, the greatest IR difference (78.8%) was between Kentucky (5.9/100, 000) and Los Angeles (3.3/100, 000) in 30‐ to 34‐year‐olds ( p < .0001). Within the Black population, the greatest difference (136.2%) was between rural Georgia (30.7/100, 000) and California excluding San Francisco‐Oakland/San Jose‐Monterey/Los Angeles (13/100, 000) in 40‐ to 44‐year‐olds ( p = 0003). Conclusion: Marked geographic EOCRC disparities exist with disproportionately high IRs in Alaska Natives, Hawaii, and southern registries. Geographic intra‐racial disparities are present within White and Black populations. In Blacks, there are disproportionately high EOCRC IRs in rural Georgia. Although vigilance is required in all populations, attention must be paid to these higher risk populations. Potential interventions include assuring early investigation of symptoms, targeting modifiable risk factors and utilizing earlier age 45 screening options supported by some guidelines. Abstract : This analysis of SEER 18 early‐onset colorectal cancer data reveals marked disparities by geography and within racial groups (intra‐racial) across the United States. This data can be used to target public health interventions and guide future studies on etiology.